G345 A systematic review and meta-analysis of chronic and integrated care models to improve child health. (May 2019) - Satherley, R; Scotney, E; Newham, J; Forman, JR; ElSherbiny, M; Lingam, R; Wolfe, I
Abstract : Introduction: New models of healthcare have largely focussed on adults, with increasing interest in integrated care. Integrated care models have been identified as a promising solution by policy makers, children and young people (CYP), to target the gaps in healthcare delivery for CYP with on-going conditions. However, there has been limited work on developing and evaluating integrated models of child healthcare. This systematic review and meta-analysis assessed the effects of integrated care on child health, health service use, and healthcare quality for CYP with on-going conditions. Methods: Articles were eligible for the review if they 1) reported randomised controlled trials (RCTs), published between 1996 and 2018; 2) evaluated an integrated healthcare intervention designed to improve child health; 3) included CYP (0–18 years) with an on-going health condition; 4) included at least one health-related outcome. Descriptive data was synthesised for all included papers, and data homogeneity allowed further meta-analyses to explore the effects of integrated care interventions compared with usual care, on health-related quality of life (QOL) and number of emergency department visits. Results: Twenty-three randomised controlled trials were identified, describing 18 interventions. Studies had medium risk of bias. Improvements were found for quality of care (87% of interventions found a positive effect for intervention) and child health (39% found a positive effect for intervention). The meta-analyses found that integrated care interventions have a positive effect in improving QOL over usual care (n=5 trials; SMD=0.24; 95% CI=0.03, 0.44; p=0.02), but no significant difference across groups for emergency department contacts (n=5 trials;OR=0.82; 95% CI=0.53, 1.26; p=0.37). Conclusion: Integrated care interventions for CYP with on-going conditions may deliver improved QOL for children, health, and quality of care. However, no conclusions can be made about the direction or magnitude of the effect for integrated care interventions on emergency department contacts in CYP with on-going conditions. Only 23 RCTs were included in this review, which were of moderate quality, highlighting the need for more robust trials to inform current health service delivery in this area and fully establish the effectiveness of integrated healthcare interventions on CYP outcomes.